Calcium-Regulating Hormonal System and HMGB1 in Cardiomyopathies - Harutyunyan, Knarik R.; Abrahamyan, Hermine T.; Adamyan, Satenik H.; Mkrtchian, Souren; Ter-Markosyan, Anna S. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Calcium ions play a key role in the heart's functional activity. The steadystate levels of calcium are contingent on the calcium regulating hormonal system, impairment of which might result in the development of cardiac pathology. An important role in these processes is also attributed to the specific inflammatory mediator, HMGB1, one of the damage-associated molecular patterns (DAMPs) released by immune cells or cell damage. Objective: This study investigated the cardioprotective potential of the calcium-regulating hormonal system in cardiomyopathies with an emphasis on the possible role of HMGB1. Methods: Ca2+ and inorganic phosphate levels were determined in the serum using an electrolyte analyzer and spectrophotometric analyzer correspondingly. The 1-34 fragment of parathyroid hormone (PTH), calcitonin, vitamin D, and HMGB1 were detected using ELISA kits. Results: The levels of PTH, calcitonin, phosphate, and HMGB1 were found elevated in females suffering from cardiomyopathy. The same tendency was observed in men; however, statistically significant changes were registered only for PTH and phosphate. Conclusion: It can be suggested that among other reasons, the decrease of the left ventricular function in cardiomyopathy patients can be linked to the high HMGB1, whereas the activation of the calciumregulating system as manifested by the elevated PTH aims at restoration of calcium homeostasis and thus have positive, i.e. cardioprotective consequences.
Keywords: calcitonin